Pengaruh Kesakitan pada Nefron Terhadap Terjadinya Penyakit Gagal Ginjal - Elsa Trisna Sari; Nur Aini Fatna Fadilla; Tyara Avrilyanti Ghea Indriansyah; Liss Dyah Dewi Arini (Student Scientific Creativity Journal, 2025)
Nephrons are the smallest functional units in the kidneys that are responsible for filtering blood, regulating fluid balance, and excreting waste through urine. When nephrons are damaged or diseased, kidney function can be significantly impaired. Nephron damage is usually caused by various factors, such as hypertension, diabetes, kidney infections, or certain drug toxicity. In the early stages, nephron damage can cause a decrease in glomerular filtration rate (GFR). As a result, metabolic waste products such as urea and creatinine accumulate in the blood, known as azotemia. Over time, progressive damage to the nephrons can trigger chronic kidney disease (CKD). In more severe cases, when most of the nephrons are no longer functioning, the kidneys lose their ability to maintain the body's homeostasis. This results in electrolyte imbalance, metabolic acidosis, and excess fluid buildup, known as end-stage renal disease (ESRD). At this stage, patients require renal replacement therapy such as dialysis or kidney transplantation to survive. Prevention of nephron damage is very important, including through the management of comorbidities such as diabetes and hypertension, adequate fluid intake, and avoiding exposure to toxic substances that damage the kidneys. Thus, the risk of kidney failure can be minimized.